“Estimación del carbono en la biomasa aérea del café (coffea arabica var. Catimor) bajo sombra de guaba (inga edulis) en la provincia de Lamas-Perú” - Isminio Ramírez, Marco Antonio (2006)
The present work of lnvestigation has like 1 title "ESTIMATE OF THE RETAINED CARBON IN THE BIOMASS OF THE STRATUM - COFFEE (Arabic Coffea) LOW SHADE DE GUABA (Inga sp.) IN THE COUNTY OF YOU LICK-PERU.", the objectives were to estímate the quantity of carbon retained in the trash, in the arbustiva ones, in the air biomass and in the 5 superior cm of the floor, in a system agroforestal of coffee low shade of Inga sp. and to determine the relative proportion of the contribution in the systems agroforestales and to establish the relationship among their components, in the district of Rumizapa, county of you Lick, Department of San Martín. Likewise the Design of Blocks was used Totally at random with 5 treatments and 5 repetitions. The treatments were: T1 (3 year-old coffee), T2 (4 yearold coffee), T3 (5 year-old coffee), T4 (6 year-old coffee) and Ts (primary forest). In the results one can observe that, the biggest quantity in carbon in comparison to the other evaluated parameters was obtained in the arboreal biomass of the primary forest, with a value of 79 008.40 Kg. C/ha, followed by the floor with 37 500 Kg. C/ha (primary forest), the trash with 7 900.46 Kg. C/ha (6 year-old coffee), and far 1 finish the herbaceous biomass with 2 408.12 Kg. C/ha (5 year-old coffee).